Interprofessional, learner-driven collaboration for innovative solutions to healthcare delivery in student-run clinics. Issue 1 (2nd January 2020) - Chen, Kevin; Kruger, Jessica; McCarther, Noria; Meah, Yasmin
ABSTRACT: Student-run clinics are settings in which learners are empowered to design service delivery. Despite shared challenges faced by these clinics in improving clinical and educational programming, information exchange and collaboration between clinics of different institutions and professions are inefficiently facilitated by existing platforms. An abridged, one-hour hackathon event was piloted at the Society of Student-Run Free Clinics' 2018 Annual Conference. During the event, interprofessional teams were guided through defining a problem, ideating and prototyping possible solutions, and sharing them with the larger group. There were 23 participants representing 16 institutions and 5 professions; most had never discussed their clinic's problems with members of other institutions before. Teams generated novel ideas that culminated from a combination of existing local best practices or focused on developing infrastructure between clinics. Feedback of the event was positive; participants felt confident to design and implement solutions and collaborate with other clinics after the event. The abridged hackathon shows promise to facilitate communication and innovation among diverse groups across institutions.